Effects of task-oriented training on upper extremity function and performance of daily activities in chronic stroke patients with impaired cognition - Park, JuHyung (Journal of Physical Therapy Science, 2016)
[Purpose] This study aimed to determine the effects of task-oriented training on upper extremity function and performance of daily activities in chronic stroke patients with impaired cognition. [Subjects and Methods] In this study, 2 chronic hemiplegic stroke patients underwent task-oriented training. The training was conducted once a day for 30 minutes, 5 times/week, for 2 weeks. The patients were evaluated 3 times before and after the task-oriented training. Changes in upper extremity function were assessed using the manual function test, and changes in the ability to carry out daily activities were assessed using the functional independence measure. [Results] The patients showed improvement in both the upper extremity function and ability to perform daily activities after task-oriented training. [Conclusion] Task-oriented training was proven effective in improving upper extremity function and ability to perform daily activities in chronic hemiplegic stroke patients with impaired cognition.